Manning Up: Modern Manhood, Rudimentary Pugilistic Capital, and Esquire Network's White Collar Brawlers. (February 2020) - Berg, Adam; Linden, Andrew D.; Schultz, Jaime
Debuting in 2013, Esquire Network's first season of White Collar Brawlers features professional-class men with workplace conflicts looking to "settle the score in the ring." In the show, white-collar men are portrayed as using boxing to reclaim ostensibly primal aspects of masculinity, which their professional lives do not provide, making them appear as better men and more productive constituents of a postindustrial service economy. Through this narrative process, White Collar Brawlers romanticizes a unique fusion of postindustrial white-collar employment and the blue-collar labors of the boxing gym. This construction, which Esquire calls "modern manhood, " simultaneously empowers professional-class men while limiting the social mobility of actual blue-collar workers. Based on a critical textual analysis that adopts provisional and rudimentary aspects of Wacquant's conception of "pugilistic capital, " we contend that Esquire Network has created a show where men are exposed to and sold an image of "modern manhood" that reifies class-based differences and reaffirms the masculine hegemony of white-collar identities.